2012
DOI: 10.1097/sla.0b013e31824e9112
|View full text |Cite
|
Sign up to set email alerts
|

Fistulotomy and Sphincter Reconstruction in the Treatment of Complex Fistula-in-Ano

Abstract: Fistulotomy with sphincter reconstruction is an effective technique for the treatment of complex fistula-in-ano. Continence and anal manometry results were improved in incontinent patients and were not jeopardized in continent ones. Fistulotomy with sphincter reconstruction is an especially suitable technique for incontinent patients with recurrent fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 15 publications
1
46
0
3
Order By: Relevance
“…The weighted average rate of sphincter dehiscence (which is regarded as the most feared postoperative complication related to FIPS) was 2.2 %, and it ranged from 0 to 8.3 % (Table 3). Other minor reported postoperative complications were: proctalgia or defecation disorders, urinary retention, fecal impaction, anal abscess [38], deformity [34] and wound complications [36]. The skin wound was sutured in seven studies [19,29,31,32,34,37,38] with a weighted average healing rate without dehiscence of 68.9 % (range 28.6-100 %) ( Table 3).…”
Section: Clinical Results: Success and Morbiditymentioning
confidence: 99%
See 4 more Smart Citations
“…The weighted average rate of sphincter dehiscence (which is regarded as the most feared postoperative complication related to FIPS) was 2.2 %, and it ranged from 0 to 8.3 % (Table 3). Other minor reported postoperative complications were: proctalgia or defecation disorders, urinary retention, fecal impaction, anal abscess [38], deformity [34] and wound complications [36]. The skin wound was sutured in seven studies [19,29,31,32,34,37,38] with a weighted average healing rate without dehiscence of 68.9 % (range 28.6-100 %) ( Table 3).…”
Section: Clinical Results: Success and Morbiditymentioning
confidence: 99%
“…The use of complete bowel preparation was described in seven series [19,29,33,34,36,38,39], while Ratto et al [20] preferred enemas. Ten studies reported pre-and/or postoperative administration of antibiotics [19,29,30,[32][33][34][36][37][38][39], and one study reported no use of antibiotics [20] ( Table 2).…”
Section: Perioperative Detailsmentioning
confidence: 98%
See 3 more Smart Citations